Drinking Water Quality and its Effects on Productive Performance and Immune Response of Layers - Abbas, Talha E.E.; Elzubeir, Elfadil A.; Arabbi, Omer H. (International Journal of Poultry Science, 2008)
Samples of water were taken from two sources (Nile and well). Physical, chemical and bacteriological analysis of samples revealed that, levels of salinity, hardness, alkalinity, Ca, Mg, Na and K in the well water were higher than those in the Nile water. Total bacterial count was higher in the Nile water than in the well water. Then an experiment was carried out to detect the effects of different sources of water on productive performance and immune response of immunized layers. The control (group A) was supplied with tap water that comes From Nile river. Group B was supplied with water from the same source and immunized with 0.2 ml of sheep red blood cells (SRBCs) at the end of the second week of the experiment. Group C was supplied with well water and immunized with SRBCs at the end of the second week of the experiment. After a 10 days interval group B and C were immunized with a second similar dose of SRBCs. different sources of water had no significant effect (P > 0.05) on water and feed consumption, water/feed consumption ratio, egg production, egg weight, feed conversion ratio, change in body weight and on the total antibodies titres of layers when immunized with SRBCs.